Philosophers and their poets : reflections on the poetic turn in philosophy since Kant - Bambach, Charles R.; George, Theodore D., 1971- (Albany : State University of New York Press, 2019)
"Several of the most celebrated philosophers in the German tradition since Kant afford to poetry an all but unprecedented status in Western thought. Fichte, Hegel, Nietzsche, Heidegger, and Gadamer argue that the scope, limits, and possibilities of philosophy are intimately intertwined with those of poetry. For them, poetic thinking itself is understood as intrinsic to the kind of thinking that defines philosophical inquiry and the philosophical life, and they developed their views through extensive and sustained considerations of specific poets, as well as specific poetic figures and images. This book offers essays by leading scholars that address each of the major figures of this tradition and the respective poets they engage, including Schiller, Archilochus, Pindar, Hölderlin, Eliot, and Celan, while also discussing the poets' contemporary relevance to philosophy in the continental tradition. Above all, the book explores an approach to language that rethinks its role as a mere tool for communication or for the dissemination of knowledge. Here language will be understood as an essential event that opens up the world in a primordial sense whereby poetry comes to have a deeply ethical significance for human beings. In this way, the volume positions ethics at the center of continental discourse, even as it engages philosophy itself as a discourse about language attuned to the rigor of what poetry ultimately expresses."--
Acknowledgments -- Introduction: Poetizing and thinking / Charles Bambach and Theodore George -- Chapter 1. On the poetical nature of philosophical writing: a controversy over style between Schiller and Fichte / María del Rosario Acosta López -- Chapter 2. Fichte and Schiller correspondence, from Fichte's Werke, Vol. 8 (De Gruyter) / Christopher Turner, translator -- Chapter 3. Hegel, romantic art, and the unfinished task of the poetic word / Theodore George -- Chapter 4. Who Is Nietzsche's Archilochus? Rhythm and the problem of the subject / Babette Babich -- Chapter 5. Untimely meditations on Nietzsche's poet-heroes / Kalliopi Nikolopoulou -- Chapter 6. Heidegger's Ister lectures: ethical dwelling in the (foreign) homeland / Charles Bambach -- Chapter 7. Remains: Heidegger and Hölderlin amid the ruins of time / William McNeill -- Chapter 8. The poietic momentum of thought: Heidegger and poetry / Krzysztof Ziarek -- Chapter 9. Learning from poetry: on philosophy, poetry, and T. S. Eliot's Burnt Norton / Günter Figal -- Chapter 10. An "almost imperceptible breathturn": Gadamer on Celan / Gert-Jan van der Heiden -- Chapter 11. Hölderlin's Empedocles poems / Max Kommerell, trans., Christopher D. Merwin and Margot Wielgus -- Contributors -- Index.
Includes bibliographical references and index.
Print version record; online resource viewed January 25, 2021.
JSTOR
Keywords: Philosophers -- History; Philosophy, Modern; Poetry; Poetry as Topic; Philosophes -- Histoire; Poésie.; poetry; PHILOSOPHY; Aesthetics; Phenomenology; Movements; Philosophers; Philosophy, Modern; Poetry; Electronic books; History